Boosting Spice Production under Coconut Gardens of Kerala: Maximizing Yield of Turmeric with Balanced Fertilization - M. Meerabai, B.K. Jayachandran, K.R. Asha, and V. Geetha (Better Crops International Vol. 14, No. 2, November 2000, 2000)
A two-year field study was conducted on turmeric intercropped under partial shade of coconut. Results indicated that turmeric responded to higher nitrogen (N) and potassium (K) fertilizer application. Proper nutrition produced higher yield and net profit compared to turmeric supplied with state fertilizer recommendations.